2011
DOI: 10.1007/s11357-011-9266-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term training induces a healthy inflammatory and endocrine emergent biomarker profile in elderly men

Abstract: The objective of the present study was to investigate the changes in a large panel of emergent geriatric biomarkers in long-term trained elderly men to analyze the effects of long-term exercise on an aged population. We collected blood samples from two groups of male volunteers older than 65 years who maintain a measure of functional independence: one group of sedentary subjects without a history of regular physical activity and the other of subjects who have sustained training, starting during adulthood (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
1
24
1
1
Order By: Relevance
“…This is consistent with Arai et al (2006) who found no significant difference in DHEA-S between older male runners and those who were sedentary, and Traustadottir et al (2004) who reported no differences in cortisol levels between fit older women and those who were of average fitness. Although this present finding is in contrast to other studies which suggest that DHEA/S is higher in endurance trained (de Gonzalo-Calvo et al 2011;Tissandier et al 2001) and moderately trained (Ravaglia et al 2001) older men. In these previous and current investigations, blood samples were collected at similar times under the same conditions (fasted, rested, etc.).…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with Arai et al (2006) who found no significant difference in DHEA-S between older male runners and those who were sedentary, and Traustadottir et al (2004) who reported no differences in cortisol levels between fit older women and those who were of average fitness. Although this present finding is in contrast to other studies which suggest that DHEA/S is higher in endurance trained (de Gonzalo-Calvo et al 2011;Tissandier et al 2001) and moderately trained (Ravaglia et al 2001) older men. In these previous and current investigations, blood samples were collected at similar times under the same conditions (fasted, rested, etc.).…”
Section: Discussioncontrasting
confidence: 99%
“…10,11 In addition, the serum IGF-1 and DHEA can be maintained at a high level by long-term training in older adults. 30 The current trial shows that physical activity was increased in the W/N and W groups. Therefore, the W/N and W groups, but not the C group, showed a great increase in the IGF-1 and DHEA-S levels.…”
Section: Discussionmentioning
confidence: 65%
“…Melatonin may also counteract or reduce those pathologies. One example is the systemic subacute inflammation which is a predominant characteristic of the aging process [109]. This low grade inflammation has been implicated in the development of a number of chronic diseases [110] and is associated with sarcopenia development as well [67,111].…”
Section: Cellular Impact Of Sarcopeniamentioning
confidence: 99%